2009
DOI: 10.1021/la902499e
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Dot-Modified Electrode in Combination with NADH-Dependent Dehydrogenase Reactions for Substrate Analysis

Abstract: A quantum dot-electrode system was developed which allows the sensitive detection of NADH (nicotinamide adenine dinucleotide). The colloidal semiconductive CdSe/ZnS nanocrystals (quantum dots) are attached to gold by chemisorption via a dithiol compound. The current signal can be triggered by illumination of the quantum-dot-modified electrode surface. Because of photoexcitation, electron-hole pairs are generated in the quantum dots, which can be detected as anodic or cathodic photocurrent. The immobilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 56 publications
1
68
0
2
Order By: Relevance
“…The addition of non-complementary DNA also hardly affected the PEC response from target DNA. Although CdS or CdTe QDs showed PEC response to oxygen, they also showed response to a variety of electron donors (Wang et al, 2009a(Wang et al, , 2009bAn et al, 2010;Schubert et al, 2010;Long et al, 2011;Zhao et al, 2012;Hao et al, 2012). However, it was found that PbS QDs showed no response to 5.0 Â 10 À 5 mol/L ascorbic acid, dopamine, uric acid or cysteine.…”
Section: Selectivity Stability and Reproducibilitymentioning
confidence: 98%
See 1 more Smart Citation
“…The addition of non-complementary DNA also hardly affected the PEC response from target DNA. Although CdS or CdTe QDs showed PEC response to oxygen, they also showed response to a variety of electron donors (Wang et al, 2009a(Wang et al, , 2009bAn et al, 2010;Schubert et al, 2010;Long et al, 2011;Zhao et al, 2012;Hao et al, 2012). However, it was found that PbS QDs showed no response to 5.0 Â 10 À 5 mol/L ascorbic acid, dopamine, uric acid or cysteine.…”
Section: Selectivity Stability and Reproducibilitymentioning
confidence: 98%
“…The extensively studied PEC sensors based on photoanodes made by n-type semiconductors (such as sensitized TiO 2 or CdS quantum dots (QDs)) showed sensitive response to a variety of reductive substances, such as ascorbic acid (Wang et al, 2009a(Wang et al, , 2009b, H 2 O 2 Tu et al, 2012; P.P. , nicotinamide adenine dinucleotide (NADH) (Schubert et al, 2010), and thio compounds (Long et al, 2011;Zhao et al, 2012). This was because the photogenerated holes of n-type semiconductors would transfer to their surface and react with the reductive substances (acting as electron donors).…”
Section: Introductionmentioning
confidence: 99%
“…Such a photoswitchable interlayer of QDs on a gold electrode allows for a spatially resolved read-out of the sensor surface at low electrode potentials (at ∼0 V vs Ag/AgCl, 1 M KCl). 24 Most NADH-based enzymatic reactions are monitored via UV spectroscopy at 345 nm where NADH (in contrast to NAD + ) displays fairly strong absorption. Numerous (clinical) assays rely on this scheme that can be operated in the kinetic and in the end point mode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to these charge carriers electrons can be transferred to or from the QDs. QDs thus can be oxidized/reduced and can serve as light-controlled redox active element and can be integrated in electrochemical signal chains [9,14-16]. The key advantage hereby is that the redox reaction of the QD surface can be virtually switched on and off by light.…”
Section: Introductionmentioning
confidence: 99%
“…We hereby put particular interest in the way of immobilization of ALP on the electrode. In previous work the enzymes were suspended in the solution above the sensor electrode [6,9]. Here we go a step further and directly immobilize the enzyme on the QD-modified electrode.…”
Section: Introductionmentioning
confidence: 99%